2023
DOI: 10.3389/fpsyg.2023.1067165
|View full text |Cite
|
Sign up to set email alerts
|

Cybervictimization and cyberbullying among college students: The chain mediating effects of stress and rumination

Abstract: The popularity of the Internet has led to an increase in cybervictimization and cyberbullying. Many studies have focused on the factors influencing cybervictimization or cyberbullying, but few have researched the mechanism that mediates these phenomena. Therefore, in this study, we use a chain mediation model to explore the mechanisms of cybervictimization and cyberbullying. This research is based on the general aggression model and examines whether stress and rumination play a mediating role in the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Accordingly, literature has found a significant positive correlation between angry rumination and cyberbullying perpetration among adolescents (Camacho et al, 2021;Gao et al, 2021;. Luo et al (2023) also confirmed that the tendency to ruminate has a significant association with an individual's cyberbullying perpetration. Moreover, Parris et al (2022) suggested that high school students who engage in social media rumination may be more likely to be cyberbullying perpetrators.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Accordingly, literature has found a significant positive correlation between angry rumination and cyberbullying perpetration among adolescents (Camacho et al, 2021;Gao et al, 2021;. Luo et al (2023) also confirmed that the tendency to ruminate has a significant association with an individual's cyberbullying perpetration. Moreover, Parris et al (2022) suggested that high school students who engage in social media rumination may be more likely to be cyberbullying perpetrators.…”
Section: Introductionmentioning
confidence: 71%
“…Compared to other negative life events, as a typical adverse event in cyberbullying scenarios, cyber victimization is more likely to lead to cyberbullying, thus creating a vicious cycle ( Sun et al, 2020 ). Prior literature has found a strong correlation between cyber victimization and cyberbullying perpetration, but the underlying mechanisms remain unclear ( Luo et al, 2023 ). Future studies could further explore the association between early cyber victimization experience and cyberbullying perpetration to examine the mechanisms underlying the role transition from victim to bully in cyberbullying incident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson and Bushman's general model of aggression (18) suggests that personal and situational factors (both referred to as input variables) influence the occurrence of aggression through present internal states (including cognition, affect, and arousal), and Kowalski et al (17) further explain cyberbullying encountering through this theoretical model. According to the general aggression model, perceived stress is an important personal factor affecting individuals' cognitive and affective states (19,20). Previous research has shown a strong association between perceived stress and aggression involving adolescents (21), and youth are more likely to engage in bullying behavior (both traditional and online) to respond to stressful life events (22).…”
Section: Perceived Covid-19 Stress and Online Aggressionmentioning
confidence: 99%